NASICON-based CO2 sensor taking Co3O4-Li2CO3 as sensitive electrode and preparation method of NASICON-based CO2 sensor

The NASICON-based CO2 sensor with a Co3O4-Li2CO3 sensitive electrode addresses sensitivity and cost issues by enhancing the three-phase interface, achieving improved sensitivity and selectivity to CO2.

CN119118711AActive Publication Date: 2024-12-13JILIN UNIVERSITY

Patent Information

Application Number
CN202411264932.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

Existing CO2 sensors, particularly NDIR sensors, face high manufacturing costs and environmental sensitivity issues, while electrochemical sensors suffer from corrosion, leakage, and poor sensitivity due to blocked pores in the three-phase interface by melted lithium carbonate.

Method used

A NASICON-based CO2 sensor with a Co3O4-Li2CO3 sensitive electrode is developed, utilizing a spin coating method to form a NASICON matrix layer on an Al2O3 ceramic tube, combined with a nickel-cadmium heating coil, to enhance sensitivity and response characteristics.

Benefits of technology

The sensor exhibits improved response performance, with 10% wt Co3O4-modified Li2CO3 showing the best results, offering high sensitivity, stability, and selectivity to CO2, and rapid response and recovery times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118711A_ABST
    Figure CN119118711A_ABST
Patent Text Reader

Abstract

The invention discloses an NASICON-based CO2 sensor taking Co3O4-Li2CO3 as a sensitive electrode and a preparation method, and belongs to the technical field of solid electrolyte type gas sensors. The sensor is composed of an Al2O3 ceramic tube, an NASICON substrate layer, a reference electrode and a sensitive electrode. The NASICON substrate layer is uniformly coated on the outer surface of the Al2O3 ceramic tube, the reference electrode and the sensitive electrode are positioned at the two ends of the outer surface of the NASICON substrate layer, and a nickel-cadmium heating coil is arranged in the ceramic tube in a penetrating manner to provide proper working temperature for the sensor; according to the present invention, the sensitive electrode material is Co3O4-modified Li2CO3, the mass fraction of Co3O4 is 5-20%, the experiment results show that the Co3O4-modified Li2CO3 effectively improves the response performance of the sensor, and the 10% wt Co3O4-modified Li2CO3 sensor has the optimal response characteristic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid electrolyte type gas sensors, and in particular relates to a NASICON-based CO2 sensor using Co3O4-Li2CO3 as a sensitive electrode and a preparation method thereof. Background Art

[0002] Excessive CO2 emissions have caused a serious greenhouse effect, and some places have caused catastrophic events such as heat waves and floods, which have caused great harm to humans. In addition, food is the primary need of the people, and many countries are facing the problem of too many people and too little land. It is particularly important to increase crop yields. Crop growers can control the CO2 content so that the growth environment of greenhouse planting reaches the optimal CO2 concentration for photosynthesis. Therefore, the development of CO2 sensors is of great significance.

[0003] Currently, NDIR sensors are widely used for carbon dioxide monitoring. NDIR sensors, the full name of which is Non-Dispersive Infrared sensors, are based on the absorption characteristics of CO2 gas molecules for infrared light of a specific wavelength. They use a broad-spectrum infrared light source to emit infrared light, which passes through a sample chamber containing CO2 gas. CO2 gas molecules absorb infrared light of a specific wavelength, causing the intensity of the infrared light to weaken. By measuring changes in the intensity of infrared light, the NDIR sensor can calculate the CO2 gas concentration. NDIR sensors have the advantages of large response, good stability, and long life, but they also have limitations such as high manufacturing costs and being greatly affected by the environment. For example, in high humidity and high temperature environments, the test error is large.

[0004] So far, there have been many reports on electrochemical CO2 gas sensors. In 1953, Clark, LC and others developed the first classic liquid electrolyte gas sensor - Clark sensor. Clark sensor was originally used for O2 testing. With the efforts of researchers, CO2 gas sensors in the form of electrolytes were developed to achieve CO2 gas testing. However, electrolytes are generally corrosive and prone to leakage, causing pollution. They also attenuate the sensing signal and shorten the life of the sensor. In order to overcome these problems, people actively developed solid electrolyte gas sensors.

[0005] In 1977, Canadian scholar Gauthier successfully prepared a CO2 sensor using K2CO3 as a solid electrolyte for the first time. Since then, research on electrochemical gas sensors based on solid electrolytes has been rapidly developed, with the focus shifting to the use of NASICON (Na3Zr2Si2PO 12) as a solid electrolyte, and a ceramic tube as a substrate to build a tubular structure. Research attempts to use Li2CO3 is often used as a sensitive material. In order to better form a sensitive electrode, a melt quenching method is used to prepare a sensitive electrode. However, the melted lithium carbonate easily blocks some pores, preventing some CO2 from entering the three-phase interface (TPB: the junction of gas, sensitive electrode and NASICON matrix) for reaction, resulting in low sensitivity. In order to allow as much CO2 as possible in the test environment to enter the TPB reaction, we used Co3O4 to modify Li2CO3 to improve the response characteristics. Summary of the invention

[0006] The NASICON-based equilibrium potential tubular CO2 sensor with Co3O4-Li2CO3 as the sensitive electrode described in the present invention is composed of an Al2O3 ceramic tube, a NASICON substrate layer, a reference electrode and a sensitive electrode; the NASICON substrate layer is evenly coated on the outer surface of the Al2O3 ceramic tube, the reference electrode and the sensitive electrode are located at both ends of the outer surface of the NASICON substrate layer, and a nickel-cadmium heating coil is inserted inside the ceramic tube to provide a suitable working temperature for the sensor; the sensitive electrode material is Li2CO3 modified with Co3O4, wherein the mass fraction of Co3O4 is 5-20%, and experiments have found that Li2CO3 modified with Co3O4 effectively improves the response performance of the sensor, and the Li2CO3 sensor modified with 10%wt Co3O4 has the best response characteristics.

[0007] The preparation method of the NASICON-based equilibrium potential type tubular CO2 sensor using Co3O4-Li2CO3 as the sensitive electrode of the present invention comprises the following steps:

[0008] (1) Preparation of NASICON matrix layer: Select an Al2O3 ceramic tube of appropriate length, clean and dry it; grind the NASICON powder into ultrafine powder of 2000-4000 mesh, add an appropriate amount of deionized water and continue grinding into a paste slurry (the mass volume ratio of NASICON powder to deionized water is 1g:0.2-0.4mL), and then use a spin coating method to evenly coat the paste slurry on the outer surface of the Al2O3 ceramic, and then place it in a muffle furnace and sinter it at 800-1000℃ for 6-8h to form a NASICON matrix layer with a thickness of 0.5-1mm on the outer surface of the Al2O3 ceramic tube;

[0009] (2) Making a ring electrode: dip gold paste on the left and right ends of the NASICON substrate layer to form 2 to 3 parallel gold paste rings, connect the gold paste rings at one end to form a whole as a sensitive electrode base, and connect the gold paste rings at the other end to form another whole as a reference electrode; use platinum wire to lead out electrode leads on the formed sensitive electrode base and reference electrode, and then sinter at 800 to 1000°C for 20 to 40 minutes;

[0010] (3) Making a sensitive electrode: Co3O4 and Li2CO3 are mixed and fully ground for 8 to 20 minutes to obtain a sensitive material, wherein the mass fraction of Co3O4 is 5 to 20%; the sensitive material and deionized water are mixed to obtain a slurry (the mass volume ratio of the sensitive material to the deionized water is 1 g: 0.1 to 0.3 mL), the slurry is applied to the surface of the sensitive electrode base, the moisture is dried under an infrared lamp, and the mixture is sintered in a tube furnace at 700 to 750°C for 1 to 3 minutes, and then quickly taken out and cooled to room temperature, thereby preparing a sensitive electrode with a thickness of 0.1 to 0.3 mm on the NASICON substrate layer;

[0011] (4) Preparation of sensor: A 20-40Ω nickel-cadmium heating coil is passed through the interior of an Al2O3 ceramic tube, and after welding and packaging, the NASICON-based equilibrium potential tubular CO2 sensor with Co3O4-Li2CO3 as the sensitive electrode is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 : The XRD pattern of the NASICON material prepared by the sol-gel method in Example 1 is compared with the standard spectrum. The spectrum is consistent with the standard card 35-0412, indicating that NASICON has been prepared;

[0013] Figure 2 :Tube sensor manufacturing process and structural diagram;

[0014] Figure 3 :XRD patterns of Li2CO3 doped with different mass fractions nwt% Co3O4 (n=0, 5, 10, 20) after sintering at 730℃ for 2min, indicating that Co3O4 and Li2CO3 are mixed and LiCoO2 is indeed generated under high temperature conditions;

[0015] Figure 4:SEM images of a 2mm×2mm smooth YSZ plate coated with a NASICON layer and then coated with a sensitive material before sintering at 730℃ for 2min; (a) The sensitive material in the image is Li2CO3; (b) The sensitive material in the image is 5wt% Co3O4-Li2CO3; (c) The sensitive material in the image is 10wt% Co3O4-Li2CO3; (d) The sensitive material in the image is 20wt% Co3O4-Li2CO3. This shows that as the Co3O4 content increases, more gas is generated, and more pores are created in the sensitive material. Figure 3 This indicates that the following reaction occurred during the formation of the sensitive material: 4Co3O4+6Li2CO3+O2=12LiCoO2+6CO2;

[0016] Figure 5 : Continuous response diagram of the sensor in experimental group 3 from 500ppm CO2 to 50000ppm CO2; the potential difference across the sensor decreases with the increase of CO2 concentration, and at the same CO2 concentration, the potential difference is relatively close, indicating that the sensor has good consistency.

[0017] Figure 6 : The linear relationship curve between the voltage between the two electrodes of the sensor in the experimental group 3 and the CO2 concentration has a slope of -43.6mV / decade, indicating a good linear relationship;

[0018] Figure 7 : The experimental group 3 sensor tested the response recovery time curve from air to 5400ppm CO2. The response time was 6s and the recovery time was 15s, indicating that the response recovery time of the sensor was short;

[0019] Figure 8 : The sensor in experimental group 3 continuously tested the response curve from air to 5400ppm CO2, and it can be seen that the sensor has good repeatability;

[0020] Fig. 9 : The experimental group 3 sensor tested the response curve from air to 5400ppm CO2 for 30 days, indicating that the sensor has good stability;

[0021] Fig.10 : The experimental group 3 sensor was tested for selectivity against 400ppm CH4, H2, CO, SO2, and CO2. The results show that the response to CO2 is significantly greater than that to other gases, indicating that the sensor has good selectivity.

[0022] Fig.11 : Comparison of the response recovery curve of the sensor in group 1 to 5400ppm CO2;

[0023] Fig.12: Response recovery curve of sensor in experimental group 1 to 5400ppm CO2;

[0024] Fig.13 : Response recovery curve of sensor in experimental group 2 to 5400ppm CO2;

[0025] Fig.14 : Response recovery curve of sensor in experimental group 3 to 5400ppm CO2;

[0026] Comprehensive comparison of group 1 and experimental groups 1 to 3 shows that adding Co3O4 to Li2CO3 can improve the response performance of the sensor, and the experimental group found that the response was best when 10% wtCo3O4 was added. DETAILED DESCRIPTION

[0027] Example 1

[0028] The solid electrolyte NASICON prepared by the sol-gel method is used as the ion conductive layer. The specific steps are as follows:

[0029] (1) 8.05 g of ZrOCl2.8H2O was dissolved in deionized water to prepare a solution with a concentration of 0.2 mol / L, and then placed in a constant temperature of 80°C with magnetic stirring for 10 min;

[0030] (2) Dilute concentrated ammonia water with a mass fraction of 25% (diluted by volume ratio of 1:4) and place it in a separatory funnel and drip it into the solution prepared in step (1) to generate a white ZrO(OH)2 precipitate. When the pH value of the solution reaches 10, the titration is terminated. The precipitation reaction formula is:

[0031] ZrOCl2+2NH4OH==ZrO(OH)2↓+2HN4Cl

[0032] (3) Wash the precipitate obtained in step (2) with deionized water by centrifugation three times to obtain pure ZrO(OH)2, wash the precipitate with as little deionized water as possible and pour it into a beaker, and then stir it magnetically at a constant temperature of 80°C for 10 minutes for later use;

[0033] (4) Add 68% concentrated HNO3 to deionized water for dilution (diluted by volume ratio of 1:4), and drop the diluted HNO3 into the ZrO(OH)2 precipitate obtained in step (3) until the precipitate is completely dissolved to obtain a soluble ZrO(NO3)2 solution. The dissolution reaction formula is:

[0034] ZrO(OH)2+2HNO3==ZrO(NO3)2+2H2O

[0035] (5) Take 3.18 g of NaNO3 and dissolve it in 5 mL of deionized water to obtain a NaNO3 solution;

[0036] (6) Take 1.65 g of (NH4)2HPO4 and dissolve it in 5 mL of deionized water to obtain a (NH4)2HPO4 solution;

[0037] (7) At 80°C, 5.54 mL of ethyl orthosilicate, 5.54 mL of anhydrous ethanol and 3.97 mL of H2O were mixed successively and magnetically stirred to be uniform. After silica gel was formed, the (NH4)2HPO4 solution, ZrO(NO3)2 solution and NaNO3 solution obtained above were dripped into the silica gel in sequence at a uniform speed, and the temperature was kept constant at 80°C with stirring to obtain a uniform sol.

[0038] (8) drying the sol prepared in step (7) at 100° C. for 24 hours to obtain a xerogel;

[0039] (9) The dry gel obtained in step (8) was placed in a muffle furnace and sintered at 900° C. for 10 hours. After cooling to room temperature, it was fully ground to obtain about 60 g of NASICON powder, which was placed in a drying tower for later use.

[0040] Example 2

[0041] The preparation method of the NASICON-based equilibrium potential type tubular CO2 sensor using Co3O4-Li2CO3 as the sensitive electrode comprises the following steps:

[0042] (1) Preparation of NASICON substrate layer: Select an Al2O3 ceramic tube with a length of 6 mm, a wall thickness of 0.4 mm, and an outer diameter of 1.2 mm, wash it with deionized water to remove surface dust, and then dry it; grind the NASICON powder prepared by the sol-gel method into a 3000-mesh ultrafine powder, add an appropriate amount of deionized water and continue grinding it into a paste slurry (the mass volume ratio of NASICON powder to deionized water is 1g:0.3mL), and then use a spin coating method to evenly coat the paste slurry on the surface of the Al2O3 ceramic tube, and then place it in a muffle furnace and sinter it at 900°C for 6h to form a NASICON substrate layer with a thickness of 0.5 mm;

[0043] (2) Making ring electrodes: Use a pen to dip gold paste and apply three and two parallel gold paste rings on the left and right ends of the NASICON substrate surface, respectively. The width of the gold paste ring is 0.1 mm, the spacing between the gold paste rings is 1 mm, and the thickness of the gold paste ring is 0.05 mm. The three adjacent gold paste rings in front are connected as a whole by gold paste as a sensitive electrode base, and the two adjacent gold paste rings in the back are connected as another whole by gold paste as a reference electrode; fold the platinum wire in half and lead out the electrode leads on the formed sensitive electrode base and reference electrode, respectively, and then sinter at 900°C for 30 minutes;

[0044] Comparative group 1: Take an appropriate amount of Li2CO3 and grind it in a mortar, drop an appropriate amount of deionized water into it to make a slurry (the mass volume ratio of the sensitive material to the deionized water is 1g:0.2mL), use a stroke pen to dip the slurry into the outer surface of the sensitive electrode base, and apply it repeatedly to make the sensitive material form a thin film on the gold mesh with a thickness of 0.2mm. Place it under an infrared lamp for drying, place the dried device on a porcelain boat, sinter it in a tubular furnace at 730℃ for 2min, take it out and cool it to room temperature, then insert a 30-ohm nickel-cadmium heating wire, and then weld the six legs to the hexagonal tube socket to obtain the sensor described in comparative group 1.

[0045] Implementation Group 1: Co3O4 and Li2CO3 were mixed in a mass ratio of 5:95 to obtain a sensitive material of 5wt% Co3O4-Li2CO3. An appropriate amount was taken and ground in a mortar, and an appropriate amount of deionized water was added to make a slurry (the mass volume ratio of the sensitive material to the deionized water was 1g:0.2mL). The slurry was applied to the outer surface of the sensitive electrode base with a stroke pen, and applied multiple times so that the sensitive material formed a film on the gold mesh with a thickness of 0.2mm, and placed under an infrared lamp for drying. The dried device was placed in a porcelain boat, sintered in a tube furnace at 730℃ for 2min, taken out and cooled to room temperature, and then inserted into a 30-ohm nickel-cadmium heating wire, and then the six legs were welded to the hexagonal tube seat to obtain the sensor described in Implementation Group 1.

[0046] Implementation Group 2: Co3O4 and Li2CO3 were mixed at a mass ratio of 20:80 to obtain a 20wt% Co3O4-Li2CO3 sensitive material. An appropriate amount was taken and ground in a mortar, and deionized water was dripped into it to make a slurry (the mass volume ratio of the sensitive material to the deionized water was 1g:0.2mL), and the slurry was applied to the outer surface of the preliminary sensitive electrode base, and the coating was repeated multiple times so that the sensitive material formed a film on the gold mesh with a thickness of 0.2mm, and dried under an infrared lamp. The dried device was placed in a porcelain boat, sintered in a tube furnace at 730℃ for 2min, taken out and cooled to room temperature, and then inserted into a 30-ohm nickel-cadmium heating wire, and then the six legs were welded to the hexagonal tube seat to obtain the sensor described in Implementation Group 2.

[0047] Experimental group 3: Co3O4 and Li2CO3 were mixed at a mass ratio of 10:90 to obtain a 10wt% Co3O4-Li2CO3 sensitive material. An appropriate amount was taken and ground in a mortar, and deionized water was dripped into it to make a slurry (the mass volume ratio of the sensitive material to the deionized water was 1g:0.2mL). The slurry was applied to the outer surface of the sensitive electrode base, and the coating was repeated multiple times to form a film of the sensitive material on the gold mesh with a thickness of 0.2mm. The dried device was placed in a porcelain boat and sintered in a tube furnace at 730℃ for 2min. After being taken out and cooled to room temperature, a 30-ohm nickel-cadmium heating wire was inserted, and then the six legs were welded to the hexagonal tube seat to obtain the sensor described in experimental group 3.

[0048] The voltage data under different CO2 gas concentrations are collected in real time by connecting the electrode leads of the sensor's sensitive electrode and reference electrode to a Rigol digital multimeter. The nickel-cadmium heating wire is connected to a DC power supply to provide the sensor with a suitable working temperature, which is achieved by adjusting the current passing through the nickel-cadmium heating wire. The ideal concentration of the sample gas is obtained by static gas distribution method, and the graph is drawn using Origin Pro2018.

Claims

1. A method for preparing a NASICON-based equilibrium potential tubular CO2 sensor using Co3O4-Li2CO3 as a sensitive electrode, the steps of which are as follows: (1) Preparation of NASICON matrix layer: Select an Al2O3 ceramic tube of appropriate length, wash and dry it; grind the NASICON powder into ultrafine powder of 2000-4000 mesh, add an appropriate amount of deionized water and continue grinding into a paste slurry, then use a spin coating method to evenly coat the paste slurry on the outer surface of the Al2O3 ceramic, and then sinter at 800-1000°C for 6-8h to form a NASICON matrix layer with a thickness of 0.5-1mm on the outer surface of the Al2O3 ceramic tube; (2) Making a ring electrode: dip gold paste on the left and right ends of the NASICON substrate layer to form 2 to 3 parallel gold paste rings, connect the gold paste rings at one end to form a whole as a sensitive electrode base, and connect the gold paste rings at the other end to form another whole as a reference electrode; use platinum wire to lead out electrode leads on the formed sensitive electrode base and reference electrode, and then sinter at 800 to 1000°C for 20 to 40 minutes; (3) Making a sensitive electrode: Co3O4 and Li2CO3 are mixed and fully ground for 8 to 20 minutes to obtain a sensitive material, the sensitive material is mixed with deionized water to obtain a slurry, the slurry is dipped and coated on the surface of the sensitive electrode base, the moisture is dried under an infrared lamp, and the slurry is sintered in a tube furnace at 700 to 750°C for 1 to 3 minutes, and then quickly taken out and cooled to room temperature, thereby preparing a sensitive electrode with a thickness of 0.1 to 0.3 mm on the NASICON substrate layer; (4) Preparation of sensor: A nickel-cadmium heating coil is passed through the interior of an Al2O3 ceramic tube, and after welding and packaging, the NASICON-based equilibrium potential tubular CO2 sensor with Co3O4-Li2CO3 as a sensitive electrode is obtained.

2. The method for preparing a NASICON-based equilibrium potential tubular CO2 sensor with Co3O4-Li2CO3 as a sensitive electrode as claimed in claim 1, characterized in that: In step (1), the mass volume ratio of NASICON powder to deionized water is 1 g: 0.2-0.4 mL; in step (3), the mass volume ratio of sensitive material to deionized water is 1 g: 0.1-0.3 mL.

3. The method for preparing a NASICON-based equilibrium potential tubular CO2 sensor with Co3O4-Li2CO3 as a sensitive electrode as claimed in claim 1, characterized in that: The mass fraction of Co3O4 in the sensitive material of step (3) is 5-20%.

4. A NASICON-based equilibrium potential tubular CO2 sensor with Co3O4-Li2CO3 as sensitive electrode, characterized in that: The method is prepared by any one of claims 1 to 3.

Citation Information

Patent Citations

  • Homogeneous compound catalyst / enzyme structure, fabricating method thereof and application thereof

    CN102192938A

  • Multi-gas sensor and preparation method thereof

    CN110044989A

  • Integrated dual-function NASICON solid electrolyte gas sensor

    CN201141848Y

  • Co2 sensor and co2 detecting method

    JP2005201698A

  • Carbon dioxide sensor

    US20090095626A1

Cited By

  • Carbon dioxide sensor based on equilibrium potential type of lglzo thin film and wc-li2co3 auxiliary phase and preparation method thereof

    CN122709548A